Kajian Hukum terhadap Pelaku Tindak Pidana Kecelakaan Lalu Lintas yang Dilakukan Anak di Bawah Umur dalam Perspektif Kriminologi Studi pada Satlantas Polres Pelabuhan Belawan - Muhammad Rachwi Ritonga; Ediwarman Ediwarman; Sutiarnoto Sutiarnoto (Mahesa Research Center, 2022)
Modernization is not only in the field of electronics, but also in the field of transportation. As a result of this modernization, many young people, especially children, are affected. The role of parents to monitor the growth and development of a child is very much expected in living life in the era of modernization. In the case file Number: BP/01/I/2017/Traffic. Police Report Number: LP/0204/244/XII/2016/LL contains a case of a traffic accident crime committed by a minor that caused the death of a pedestrian. Based on research and file analysis, the diversion step is a step taken by the Belawan Harbor Police Traffic Unit in resolving the traffic accident case committed by minors and is guided by Law No. 11 of 2012 and Supreme Court Regulation No. 4 of 2014 about diversion and procedures for its implementation. Factors that cause traffic accidents committed by minors in the jurisdiction of the Belawan Harbor Police Traffic Unit, namely; parental permission, a child's habits, long distance travelled, the child's living environment and the child's social environment. The prevention efforts of the Belawan Harbor Police Traffic Unit in preventing accidents carried out by minors were hindered by the COVID-19 pandemic. However, the efforts of the Belawan Harbor Police Satlantas in handling the case file Number: BP/01/I/2017/Traffic. Police Report Number: LP/0204/244/XII/2016/LL should be appreciated and imitated by other police, because it prioritizes preventive action by taking a policy of diversion.